Shopee E-Commerce Website Quality Analysis Based on User Perception Using the Webqual Method - Fatihatul Khairan; Wing Wahyu Winarno; Asro Nasri (Publikasi Indonesia, 2024)
This study aims to analyze the quality of Shopee's e-commerce site using the WebQual method approach. Three main dimensions, namely usability, information quality, and service interaction, are used to evaluate the quality of the Shopee website from the user's point of view. This method measures users' perception of the main aspects that determine their experience in using the Shopee website. The results of the study show that although Shopee has succeeded in providing a responsive and informative platform, several areas need improvement, especially related to aspects of service interaction and the security of users' personal information. In conclusion, Shopee needs to optimize several important aspects to improve the user experience and strengthen its position as a leading e-commerce platform in Southeast Asia. Improved design and navigation of a more modern and intuitive interface can make it easier for users to navigate the platform. In addition, real-time updates of product information regarding stock and prices will help prevent user dissatisfaction. Shopee also needs to improve customer service, both with the addition of staff and technology such as advanced chatbots, to answer customer needs faster. Finally, increased security and transparency regarding transactions and protection of personal data will strengthen user trust in this platform. Through these efforts, Shopee is expected to be able to provide a better shopping experience and maintain the loyalty of its users in the midst of fierce e-commerce competition.